2022
DOI: 10.3389/fimmu.2022.953210
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral prophylaxis or preemptive therapy for cytomegalovirus after liver transplantation?: A systematic review and meta-analysis

Abstract: BackgroundTo conduct a meta-analysis with the aim of comparing the outcomes of antiviral prophylaxis and preemptive therapy for the prevention of cytomegalovirus (CMV) infection in liver transplant (LT) recipients.MethodsWe searched databases for qualified studies up until March 2022. Finally, a meta-analysis was carried out using a fixed-effect or random-effect model based on the heterogeneity.ResultsWith a total of 1834 LT patients, the pooled incidence of CMV infection and CMV disease in the overall LT reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Universal CMV prophylaxis can, however, be associated with post-prophylaxis CMV disease as well as additional drug costs. [3][4][5][6][7][8] Earlier studies suggested a lower incidence of late CMV disease in patients who underwent preemptive treatment after liver transplant. 4,5,9 A recent randomized clinical trial confirmed this finding and demonstrated a 10% lower incidence of CMV disease over 12 months after transplant in patients who underwent preemptive treatment compared to those who received universal prophylaxis for 100 days with a similar incidence of cellular rejection, neutropenia, opportunistic infection, graft loss, and all-cause mortality between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universal CMV prophylaxis can, however, be associated with post-prophylaxis CMV disease as well as additional drug costs. [3][4][5][6][7][8] Earlier studies suggested a lower incidence of late CMV disease in patients who underwent preemptive treatment after liver transplant. 4,5,9 A recent randomized clinical trial confirmed this finding and demonstrated a 10% lower incidence of CMV disease over 12 months after transplant in patients who underwent preemptive treatment compared to those who received universal prophylaxis for 100 days with a similar incidence of cellular rejection, neutropenia, opportunistic infection, graft loss, and all-cause mortality between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…CMV seronegative liver transplant recipients who have received allografts from CMV seropositive donors (donor‐positive [D+]recipient‐negative [R−]) are often given universal CMV prophylaxis because they are at an increased risk of developing CMV disease. Universal CMV prophylaxis can, however, be associated with post‐prophylaxis CMV disease as well as additional drug costs 3–8 . Earlier studies suggested a lower incidence of late CMV disease in patients who underwent preemptive treatment after liver transplant 4,5,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Hannah Kaminski explained that universal prophylaxis had been compared with pre‐emptive therapy in four RCTs 28–31 . When included in a pooled meta‐analysis, CMV infection was more likely to occur during pre‐emptive therapy than during prophylaxis (40.4% vs. 24.7%), although CMV disease incidence was low and similar with both strategies (9.4% vs. 6.4%) 21 . Included in this meta‐analysis was an RCT comparing pre‐emptive therapy with prophylaxis in D+/R‐ liver transplant recipients.…”
Section: Prevention: Antiviral Strategiesmentioning
confidence: 99%
“…The antiviral approach for the treatment of HCMV infections relies on different drugs, such as inhibitors of viral DNA polymerase, nucleoside and nucleotide analogs, pyrophosphate analogs, and terminase inhibitors [57][58][59]. Currently, various strategies such as preemptive therapy, antiviral prophylaxis, hybrid approaches (continuous surveillance after prophylaxis for HCMV viremia with preemptive therapy), and HCMV-specific immunityguided approaches could be used for the effective control of HCMV infection in transplanted patients [60]. However, antiviral prophylaxis and preemptive therapy are the most commonly used strategies worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, it has become the recommended strategy by the American Society of Transplantation; however, post-prophylaxis HCMV disease (late onset of HCMV disease) remains a well-documented and widespread problem in patients receiving antiviral prophylaxis and is found to be independently associated with mortality. On the other hand, the preemptive strategy has been shown to reduce the incidence of late-onset HCMV disease and increase the HCMV-induced immune response, but it faces logistics challenges for medical centers and patient's noncompliance with the monitoring of HCMV viremia [60,63].…”
Section: Introductionmentioning
confidence: 99%